Post-exertional increase in first-phase ejection fraction in recreational marathon runners. (May 2020) - Faconti, Luca; Parsons, Iain; Farukh, Bushra; McNally, Ryan; Nesti, Lorenzo; Fang, Lingyun; Stacey, Michael; Hill, Neil; Woods, David; Chowienczyk, Phil
Objectives: Running a marathon has been equivocally associated with acute changes in cardiac performance. First-phase ejection fraction is a novel integrated echocardiographic measure of left ventricular contractility and systo-diastolic coupling which has never been studied in the context of physical activity. The aim of this study was to assess first-phase ejection fraction following recreational marathon running along with standard echocardiographic indices of systolic and diastolic function. Design and participants: Runners (n = 25, 17 males), age (mean ± standard deviation) 39 ± 9 years, were assessed before and immediately after a marathon race which was completed in 4 h, 10 min ± 47 min. Main outcome measures: Central hemodynamics were estimated with applanation tonometry; cardiac performance was assessed using standard M-mode two-dimensional Doppler, tissue-doppler imaging and speckle-tracking echocardiography. First-phase ejection fraction was calculated as the percentage change in left ventricular volume from end-diastole to the time of peak aortic blood flow. Results: Conventional indices of systolic function and cardiac performance were similar pre- and post-race while aortic systolic blood pressure decreased by 9 ± 8 mmHg ( P  < 0.001) and first-phase ejection fraction increased by approximately 48% from 16.3 ± 3.9% to 22.9 ± 2.5% ( P  < 0.001). The ratio of left ventricular transmitral Doppler early velocity (E) to tissue-doppler imaging early annular velocity (e′) increased from 5.1 ± 1.8 to 6.2 ± 1.3 ( P  < 0.01). Conclusion: In recreational marathon runners, there is a marked increase in first-phase ejection fraction after the race despite no other significant change in cardiac performance or conventional measure of systolic function. More detailed physiological studies are required to elucidate the mechanism of this increase.